2018
DOI: 10.1111/gcb.14151
|View full text |Cite
|
Sign up to set email alerts
|

Increased body size along urbanization gradients at both community and intraspecific level in macro‐moths

Abstract: Urbanization involves a cocktail of human-induced rapid environmental changes and is forecasted to gain further importance. Urban-heat-island effects result in increased metabolic costs expected to drive shifts towards smaller body sizes. However, urban environments are also characterized by strong habitat fragmentation, often selecting for dispersal phenotypes. Here, we investigate to what extent, and at which spatial scale(s), urbanization drives body size shifts in macro-moths-an insect group characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 80 publications
4
75
1
Order By: Relevance
“…We found that traditionally and intensively managed urban green spaces cannot maintain high butterfly diversity over time, and that the general decline in species per site between 2006 and 2015 was explained by stronger declines in butterfly species richness in traditional parks, compared to ruderal and semi-natural sites. Studies on impacts of urbanization on butterflies and moths have highlighted the importance of host and food plants, heterogeneity of the urban matrix, and the quantity and quality of urban green spaces in shaping communities (Angold et al 2006;Chong et al 2014;Hardy and Dennis 1999;Kadlec et al 2008;Lizée et al 2011;Merckx et al 2018;Öckinger et al 2009). Additionally, it is evident that cities and urban landscapes can indeed contribute to biodiversity conservation by promoting biodiversityfriendly management strategies and maintaining heterogeneous urban landscapes (Kadlec et al 2008;Öckinger et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that traditionally and intensively managed urban green spaces cannot maintain high butterfly diversity over time, and that the general decline in species per site between 2006 and 2015 was explained by stronger declines in butterfly species richness in traditional parks, compared to ruderal and semi-natural sites. Studies on impacts of urbanization on butterflies and moths have highlighted the importance of host and food plants, heterogeneity of the urban matrix, and the quantity and quality of urban green spaces in shaping communities (Angold et al 2006;Chong et al 2014;Hardy and Dennis 1999;Kadlec et al 2008;Lizée et al 2011;Merckx et al 2018;Öckinger et al 2009). Additionally, it is evident that cities and urban landscapes can indeed contribute to biodiversity conservation by promoting biodiversityfriendly management strategies and maintaining heterogeneous urban landscapes (Kadlec et al 2008;Öckinger et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization has emerged as another main driver of habitat loss and fragmentation of natural and semi-natural habitats (Parris 2016). Local changes relating to loss of habitat quantity or quality are among the most important drivers of biodiversity loss in urban contexts (Beninde et al 2015;Merckx et al 2018). In addition, disturbance and management intensity typically increases with urbanization, leading to further negative effects on urban biodiversity (Beninde et al 2015;McKinney 2008;Aronson et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fragmentation sensu stricto of the remaining habitat types is expected to filter against low‐mobility species (Rochat, Manel, Deschamps‐Cottin, Widmer, & Joost, ; Sattler, Duelli, Obrist, Arlettaz, & Moretti, ), since mobility mitigates reduced resource connectivity (Cote et al, ; Parris, ). For instance, local filtering on traits known to covary with increased dispersal has been demonstrated for urban communities of vascular plants, carabid beetles and macro‐moths (Concepción, Moretti, Altermatt, Nobis, & Obrist, ; Merckx, Kaiser, & Van Dyck, ; Piano et al, ). Additionally, the UHI‐effect is expected to favour thermophilic, warm‐adapted species, a process already observed for zooplankton and beetle communities (Brans, Govaert, et al, ; Piano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, surveillance and other monitoring strategies, while comprehensive in terms of identifying population dynamics, species composition and diseases vectored during mosquito growing seasons, are not currently designed to detect adaptive changes in mosquitos across seasons. However, rapid adaptation is more common than historically recognized (Carroll, Hendry, Reznick, & Fox, 2007;Egizi et al, 2015;Gilchrist, Huey, & Serra, 2001;Keller & Taylor, 2008;Merckx, Kaiser, & Dyck, 2018;Reznick, Losos, & Travis, 2019;Schoener, 2011;While et al, 2015), and contemporary evolution during invasion is increasingly detected; this could alter predictions about the spatial extent at which surveillance programs should operate (Colautti & Barrett, 2013;Colautti & Lau, 2015;Stuart et al, 2014;Zenni, Lamy, Lamarque, & Porté, 2014). Importantly, whether traits related to invasion and range expansion are adapting rapidly across a broad range of environmental conditions is important to distinguish from local adaptation.…”
Section: Introductionmentioning
confidence: 99%